2022
DOI: 10.1021/acs.jmedchem.2c00722
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)–Tris-pyrazolylmethane Complexes Inhibit Cancer Cell Growth by Disrupting Mitochondrial Calcium Homeostasis

Abstract: While ruthenium arene complexes have been widely investigated for their medicinal potential, studies on homologous compounds containing a tridentate tris(1-pyrazolyl)methane ligand are almost absent in the literature. Ruthenium(II) complex 1 was obtained by a modified reported procedure; then, the reactions with a series of organic molecules (L) in boiling alcohol afforded novel complexes 2 – 9 in 77–99% yields. Products 2–9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 123 publications
1
30
0
Order By: Relevance
“…To develop new therapeutic agents and tools for studying m Ca 2+ , extensive research efforts have been directed toward the identification of small-molecule MCU inhibitors . To date, several organic and inorganic compounds have been discovered to possess MCU-inhibitory activity. Among these compounds, polynuclear Ru complexes are the oldest known MCU inhibitors, and recently developed analogues have shown promise for this application.…”
Section: Introductionmentioning
confidence: 99%
“…To develop new therapeutic agents and tools for studying m Ca 2+ , extensive research efforts have been directed toward the identification of small-molecule MCU inhibitors . To date, several organic and inorganic compounds have been discovered to possess MCU-inhibitory activity. Among these compounds, polynuclear Ru complexes are the oldest known MCU inhibitors, and recently developed analogues have shown promise for this application.…”
Section: Introductionmentioning
confidence: 99%
“…The 31 P NMR spectra of 2–7 show the signal related to PPh 3 as a singlet occurring in a restricted chemical shift interval (50.3–51.2 ppm), that is significantly shifted with respect to 1 ( δ = 40.1 ppm). 32 The 19 F NMR spectrum of 5 consists of a singlet at ca . −118 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…1B). 32 We found that 1 is an excellent starting material to obtain various derivatives upon substitution of one of the PPh 3 ligands, and some of these derivatives exhibited a marked antiproliferative activity against a panel of cancer cell lines, mediated in part by the inhibition of mitochondrial calcium intake. 32…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations